Applying Role-Playing Learning Model to Improve Motivation and Social Studies Learning Outcomes of Elementary School Students - Ananda, Dea; Kristin, Firosalia (EduBasic Journal: Jurnal Pendidikan Dasar, 2023)
Applying the role-playing model is important to improve elementary school students' motivation and learning outcomes. This study, thus, aims to develop a syntax of role-playing learning model in improving motivation and social studies learning outcomes of fifth-grade elementary school students. Classroom action research was the method used, and it involved both qualitative and descriptive-quantitative techniques. The data were obtained through tests to measure learning outcomes, observation sheets to see teacher and student activities in applying the role-playing model, questionnaires to gather learning motivation data, and documentation to record learning activities in the classroom. The subjects in this study were fifth grade students of the State of Elementary School of Senakin 05, totaling 20 students. Based on the data analysis results, only 31.33% of the pre-cycle participants reported increased motivation, placing them in the high category. In cycle I, it rose to 77.60% in the high category; in cycle II, it reached 96.52% in the high category. The percentage of minimum completeness criteria (KKM) also improved. Starting from pre-cycle, 100% of students failed to achieve KKM ≥ 70, averaging 54.25. Afterward, it rose in the first cycle, where 51.24% reached KKM ≥ 70, averaging 63.33. In cycle II, 83.80% attained KKM ≥ 70, averaging 90.35. The study findings have implications that the role-playing learning model can enhance learning motivation and social studies learning outcomes of fifth-grade elementary school students.